Toxicity and Antitumor Activity of a Thiophene–Acridine Hybrid - Thaís Lisboa; Daiana Silva; Sâmia Duarte; Rafael Ferreira; Camyla Andrade; Ana Luiza Lopes; Juliana Ribeiro; Davi Farias; Ricardo Moura; Malu Reis; Karina Medeiros; Hemerson Magalhães; et al. (Molecules, 2019)
The antitumor effects of thiophene and acridine compounds have been described; however, the clinical usefulness of these compounds is limited due to the risk of high toxicity and drug resistance. The strategy of molecular hybridization presents the opportunity to develop new drugs which may display better target affinity and less serious side effects. Herein, 2-((6-Chloro-2-methoxy-acridin-9-yl)amino)-5,6,7,8-tetrahydro-4H-cyclohepta[b]-thiophene-3-carbonitrile (ACS03), a hybrid thiophene−acridine compound with antileishmanial activity, was tested for toxicity and antitumor activity. The toxicity was evaluated in vitro (on HaCat and peripheral blood mononuclear cells) and in vivo (zebrafish embryos and acute toxicity in mice). Antitumor activity was also assessed in vitro in HCT-116 (human colon carcinoma cell line), K562 (chronic myeloid leukemic cell line), HL-60 (human promyelocytic leukemia cell line), HeLa (human cervical cancer cell line), and MCF-7 (breast cancer cell line) and in vivo (Ehrlich ascites carcinoma model). ACS03 exhibited selectivity toward HCT-116 cells (Half maximal inhibitory concentration, IC50 = 23.11 ± 1.03 µM). In zebrafish embryos, ACS03 induced an increase in lactate dehydrogenase, glutathione S-transferase, and acetylcholinesterase activities. The LD50 (lethal dose 50%) value in mice was estimated to be higher than 5000 mg/kg (intraperitoneally). In vivo, ACS03 (12.5 mg/kg) induced a significant reduction in tumor volume and cell viability. In vivo antitumor activity was associated with the nitric oxide cytotoxic effect. In conclusion, significant antitumor activity and weak toxicity were recorded for this hybrid compound, characterizing it as a potential anticancer compound.